Defocused Irradiation Mode of Diode Laser for Conservative Treatment of Oral Hemangioma - Fekrazad, Reza; AM Kalhori, Katayoun; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2013)
Vascular lesions rise from abnormalities in blood vessels or endothelial proliferation. Capillary hemangiomas are formed by small capillaries surrounded by a layer of endothelial cells in a connective tissue stroma. Various treatments are used for these conditions like excisional surgery, sclerotherapy, and recently laser irradiation. In this case study, we report successful treatment of intraoral capillary hemangioma by gallium/aluminum/arsenide (GaAlAs) laser. A 29 year old woman with a red lesion on the upper side of the right maxillary premolar was referred to private dental office. The Diode laser with wavelength of 810 nm was selected for treatment of the lesion in defocused mode by output power of 4 W in continuous mode. No bleeding was observed during surgery which provided better vision for surgeon and resulted in a minimally invasive procedure. According to results, Diode laser can be considered as a conservative modality in treatment of oral capillary hemangioma, especially in the esthetic zone.